Does planning help for execution? The complex relationship between planning and execution - Li, Zhaojun (PLoS One, 2020)
Planning and execution are two important parts of the problem-solving process. Based on related research, it is expected that planning speed and execution speed are positively correlated because of underlying individual differences in general mental speed. While there could also be a direct negative dependency of execution time on planning time, given the hypothesis that an investment in planning contributes to more efficient execution. The positive correlation and negative dependency are not contradictory since the former is a relationship across individuals (at the latent variable level) and the latter is a relationship within individuals (at the manifest variable level) after controlling for across-individual relationships. With two linear mixed model analyses and a factor model analysis, these two different kinds of relationships were examined using dependency analysis. The results supported the above hypotheses. The correlation between the latent variables of planning and execution was found to be positive and the dependency of execution time on planning time was found to be negative in all analyses. Moreover, the negative dependency varied among items and to some extent among persons as well. In summary, this study provides a clearer picture of the relationship between planning and execution and suggests that analyses at different levels may reveal different relationships.